Kesesuaian Lahan Untuk Tanaman Pangan di Kabupaten Madiun - Muhammad Muhammad; Uftori Wasit (Gontor AGROTECH Science Journal, 2015)
The production areas of food crops reported fluctuating during 2005 to 2009 reported by Mitra Usaha Tani. The datas showed that the production areas of rice was decresed. In contrast, its corn, cassava and sweet potato were decreased. It is necessary to increase the food production area through government policy. Analysis of land suitability for crops with a Geographic Information System (GIS) is one of the basic for policy-making and the development of technical suggestions in the agricultural sector. This research used grid-type survey method. In this case, the soil properties compared to the factor class of land suitability for particular plant based on modifi ed of FAO 1976) and Sys et. al. (1993) according to the local conditions of Madiun. The aim of this research was to evaluate the land in Madiun. It could be recomand to increase the production area of rice, corn, peanuts, bean, soybean, cassava and sweet potato. The result showed that land suitability for areas of rice production was 41.347 ha, corn 42.909 ha, peanut 41.547 ha, bean 42.909 ha, soybean 41.927 ha, cassava 41.537 ha, and sweet potato 41.537 ha.